Optimization of Exercise Countermeasures for Human Space Flight - Lessons from Terrestrial Physiology and Operational Implementation - Weber, Tobias; Paul Richard Scott, Jonathan; Andrew Green, David (Frontiers Media SA, 2020)
Human spaceflight has required space agencies to study and develop exercise countermeasure (CM) strategies to manage the profound, multi-system adaptation of the human body to prolonged microgravity (μG). Future space exploration will present new challenges in terms of adaptation management that will require the attention of both exercise physiologists and operational experts. In the short to medium-term, all exploration missions will be realised using relatively small vehicles/habitats, with some exploration scenarios including surface operations in low (<1G) gravity conditions. The evolution of CM hardware has allowed modern-day astronauts to return to Earth with, on average, relatively moderate levels μG-induced adaptation of the musculoskeletal (MS) and cardiovascular (CV) systems. However, although the intense use of CM has attenuated many aspects of MS and CV adaptation, on an individual level, there remains wide variation in the magnitude of these changes. Innovations in CM programs have been largely engineering-driven, with new hardware providing capability for new modes of exercise and a wider range of exercise protocols, which, in turn, has facilitated the transfer of traditional, but effective, terrestrial concepts based around high frequency resistance (multiple-set, multiple repetition) and mediumintensity continuous aerobic training. As a result, International Space Station (ISS) CM specialists have focused their efforts in these domains, taking advantage of hardware innovations as and when they became available. However, terrestrial knowledge in human and exercise physiology has expanded rapidly during the lifetime of the ISS and, consequently, there is potential to optimize current approaches by re-examining terrestrial knowledge and identifying opportunities to implement this knowledge into operational practices. Current terrestrial knowledge in exercise physiology is the product of a large number of intervention studies in which the variables that contribute to the effects of physical activity (mode, frequency, duration, intensity, recovery) have been controlled and systematically manipulated. However, due to limited opportunities to perform intervention studies in both spaceflight analogues - head-down bed rest (HDBR) being considered the 'gold standard' - and spaceflight itself, it will not be possible to systematically investigate the contribution of these factors to the efficacy of in-flight CM. As such, it will be necessary to draw on terrestrial evidence to identify solutions/strategies that may be best suited to the constraints of exploration and prioritise specific solutions/strategies for evaluation in HDBR and in flight.